Real-time SOSM super-twisting combined with block control for regulating induction motor velocity - Morfin Garduño, Onofre Amador (2018)
On this paper, a robust velocity controller applied to a three-phase squirrel-cage induction motor under variable load conditions is designed. The induction motor drives an induction generator representing the load which freely delivers the generated power to the utility grid. The closed-loop scheme is designed at alpha-beta coordinate frame and is based on the linearization block control technique in combination with the super-twisting algorithm. The controlled output variables are the angular mechanical velocity and the square modulus of rotor ux linkages. The motor reference velocity is set up by a pulse train above the synchronous velocity and, consequently, the impelled induction machine operates in generator mode; meanwhile, the reference of rotor ux square modulus varies according to load condition of the induction motor. In order to estimate the non-measurable variables, both a rotor ux linkages observer and a load torque observer are designed. For the first one, a non-linear state observer using fi rst order sliding modes is applied at alpha-beta coordinate frame and, for the second one, a Luenberger reduced asymptotic observer is used. The validation of the robustness for the proposed velocity controller is performed in a real-time experiment using a work-bench.